Floral nectar production and nectary structure of a bee-pollinated shrub from Neotropical savanna - Guimarães, E. [UNESP]; Nogueira, A.; Machado, S. R. [UNESP] (German Botanical Society and The Royal Botanical Society of the Netherlands, 2015)
Biotic pollination is critical for tropical ecosystem functioning, and nectar plays an essential role as it represents the main trophic resource for pollinators. Nevertheless, little is known about the mechanisms that underlie its production, which is essential for understanding the basis of nectar-mediated interactions in ecological and evolutionary approaches. Therefore, this study explores the relationship between the nectar secretion pattern and nectary functional changes in Anemopaegma album, a bee-pollinated species. We analysed the pattern of nectar production under field conditions and investigated floral nectary structural changes in two different developmental stages using light, transmission and scanning electron microscopy. We measured 30.95 ± 23.02 μl (mean ± SD, n = 30) of nectar accumulated inside the nectar chamber (29.26 ± 3.48% sucrose equivalents) at the moment of flower opening. Nectar removal did not influence the pattern of floral nectar production in terms of volume or total sugar but reduced the concentration of the nectar produced during the first 24 h of anthesis. The nectary consisted of an epidermis, a nectary parenchyma and a subnectary parenchyma supplied only by phloem. Starch grains decreased in size and abundance from the subnectary parenchyma toward the epidermis. We observed the degradation of starch grains and incorporation of amyloplasts into vacuoles at the pre-anthesis stage as well as the transformation of amyloplasts into elaioplasts during anthesis. Nectar secretion was continuous during the A. album flower life span, which was related to the functional features of its floral nectary, especially the presence of starch stored in the parenchyma.
Keywords: Anemopaegma album; Floral nectar dynamics; Nectary ultrastructure; Plant-pollinator interaction